Development of Microorganisms Capable of Absorbing Environmental Pollutants through Synthetic Biological Engineering - Tri Putri Wahyuni; Atyka Trianisa; Silvira Ilhami; Melati Latifah (CV. Get Press Indonesia, 2024)
In Indonesia, environmental pollution is a major concern, especially in industrialised and urban areas. The use of synthesised microorganisms can be an innovative solution to rehabilitate the damaged ecosystems in this region. In this research, an innovative approach based on synthetic biological engineering will be developed to create microbes that have an optimal capacity to absorb and decompose various types of environmental pollutants, such as heavy metals (Pb and Hg), hydrocarbons (benzene), and organic waste (phenol). The results show that the engineered bacteria Escherichia coli, Pseudomonas putida, Bacillus subtilis, and Alcaligenes eutrophus showed high pollutant removal efficiency (85-93%) under laboratory conditions. These results support the potential of synthetic biology technology as an innovative solutions in bioremediation of polluted environments. This research makes a real contribution to green technology innovation in environmental pollution mitigation, supporting the implementation of Sustainable Development Goals (SDGs), especially on points 6 (Clean Water) and 15 (Land Ecosystems).